RELATIONSHIP BETWEEN WOMAN-VOTERS' CHARACTERISTICS AND PARTICIPATION IN POLITICS TO THEIR PREFERENCES - Suarmini, Ni Wayan; Nuswantara, Kartika; Zain, Ismaini; Bhawika, Gita Widi; Sani, Nisfu Asrul (Jurnal Analisa Sosiologi, 2021)
Discrepancies between the number of women voters and their low legislative representation is an interesting topic of study. The laws and regulations on parties’ eligibility for elections have assigned the proportions of women candidates. These laws have been reformed continuously during elections. However, the result remained the same until the recent 2019 election. This contradicts the reality that the number of women voters, which is more than half the total population, should supply the threshold quota. Therefore, this study examines the relationship between women's preferences and other elements, including voters' characteristics and their participation in political organizations. Online questionnaires were distributed to elicit responses from 1,042 women voters. The analysis of data was performed using descriptive and inferential statistics. Primarily, inferential statistics were used to examine the relationship between the variables utilizing the Chi-Square Test of Independence. The findings confirmed that more women voted for male candidates. However, regardless of occupation, women are interested in joining political parties and assuming leadership roles. Due to the snowballing sampling procedure, it is difficult to generalize the findings of this research. For this reason, future research should target the respondents that have frequently participated in elections to accommodate more generalized findings. Keywords: woman voters, under-representation, woman legislative candidates AbstrakKesenjangan antara jumlah pemilih perempuan dengan keterwakilan legislatif yang rendah menjadi topik kajian yang menarik. Undang-undang dan peraturan tentang kelayakan partai untuk pemilihan telah menetapkan proporsi kandidat perempuan. Undang-undang ini telah direformasi terus menerus selama pemilu. Namun, hasilnya tetap sama hingga pemilu 2019 baru-baru ini. Hal ini bertolak belakang dengan kenyataan bahwa jumlah pemilih perempuan yang lebih dari separuh jumlah penduduk harus memenuhi ambang batas kuota. Oleh karena itu, penelitian ini mengkaji hubungan antara preferensi perempuan dengan elemen lainnya, termasuk karakteristik pemilih dan partisipasi mereka dalam organisasi politik. Kuesioner online dibagikan untuk mendapatkan tanggapan dari 1.042 pemilih perempuan. Analisis data dilakukan dengan menggunakan statistik deskriptif dan inferensial. Terutama, statistik inferensial digunakan untuk menguji hubungan antara variabel menggunakan Uji Independensi Chi-Square. Temuan menegaskan bahwa lebih banyak perempuan memilih calon laki-laki. Namun, terlepas dari pekerjaan, perempuan tertarik untuk bergabung dengan partai politik dan mengambil peran kepemimpinan. Karena prosedur pengambilan sampel bola salju, sulit untuk menggeneralisasi temuan penelitian ini. Untuk alasan ini, penelitian masa depan harus menargetkan responden yang sering berpartisipasi dalam pemilu untuk mengakomodasi temuan yang lebih umum.Kata kunci: Pemilih Perempuan, Keterwakilan, Caleg Perempuan